Cardiac procedural deferral during the coronavirus (COVID‐19) pandemic. Issue 5 (12th September 2020) - Yong, Celina M.; Ang, Lawrence; Welt, Frederick G. P.; Gummidipundi, Santosh; Henry, Timothy D.; Pinto, Duane S.; Cox, David; Wang, Paul; Asch, Steven; Mahmud, Ehtisham; Fearon, William F.; ,
Abstract: We aimed to examine factors impacting variability in cardiac procedural deferral during the COVID‐19 pandemic and assess cardiologists' perspectives regarding its implications. Unprecedented cardiac procedural deferral was implemented nationwide during the COVID‐19 pandemic. A web‐based survey was administered by Society for Cardiovascular Angiography and Interventions and the American College of Cardiology Interventional Council to cardiac catheterization laboratory (CCL) directors and interventional cardiologists across the United States during the COVID‐19 pandemic. Among 414 total responses, 48 states and 360 unique cardiac catheterization laboratories were represented, with mean inpatient COVID‐19 burden 16.4 ± 21.9%. There was a spectrum of deferral by procedure type, varying by both severity of COVID‐19 burden and procedural urgency ( p < .001). Percutaneous coronary intervention volumes dropped by 55% ( p < .0001) and transcatheter aortic valve replacement volumes dropped by 64% ( p = .004), with cardiologists reporting an increase in late presenting ST‐elevation myocardial infarctions and deaths among patients waiting for transcatheter aortic valve replacement. Almost 1/3 of catheterization laboratories had at least one interventionalist testing positive for COVID‐19. Salary reductions did not influence procedural deferral or speed of reinstituting normal volumes. Pandemic preparedness improved significantly over time, with the most pressing current problems focused on inadequate testing and staff health risks. During the COVID‐19 pandemic, cardiac procedural deferrals were associated with procedural urgency and severity of hospital COVID‐19 burden. Yet patients did not appear to be similarly influenced, with cardiologists reporting increases in late presenting ST‐elevation myocardial infarctions independent of local COVID‐19 burden. The safety and importance of seeking healthcare during this pandemic deserves emphasis.